Asymmetrically Varying Guide Field During Magnetic Reconnection: Particle‐In‐Cell Simulations. Issue 1 (12th January 2022) - Spinnangr, Susanne F.; Tenfjord, Paul; Hesse, Michael; Norgren, Cecilia; Kolstø, Håkon M.; Kwagala, Norah K.; Jørgensen, Therese Moretto; Pérez‐Coll Jiménez, Judit
Abstract: Using fully kinetic particle‐in‐cell modeling, we investigate how magnetic reconnection responds to a varying guide field in one of the inflow regions. We find that the reconnection rate varies significantly when the orientation of the magnetic field changes between being strictly antiparallel and having a guide field. These variations are fairly consistent with the scaling relation for asymmetric reconnection developed by Cassak and Shay (2007). However, the rate is also found to be nonlinearly modulated by changes in the ion inflow velocity. The spatio‐temporal change in the inflow velocity arises as the magnetic forces reconfigure to regions of different magnetic field strengths. The variations in the inflow magnetic field configuration allow for different gradients in the magnetic field, leading to asymmetries in the magnetic tension force. By momentum conservation, this facilitates asymmetries in the inflow velocity, which in turn affects the flux transport into the reconnection site. The outflow is found to be less laminar when the inflow varies, and various signatures of the inflow variations are identified in the outflow. Plain Language Summary: Magnetic reconnection can be described as magnetic explosions, where energy stored in magnetic fields is converted into heat and movement of particles. It can happen in all environments where magnetic fields and charged particles interact, such as in the Sun, in planetary magnetospheres, and in fusion reactors on Earth. In this article, using numerical simulations, we present new insight into how magnetic reconnection behaves when the magnetic fields vary during the reconnection process. Key Points: Spatio‐temporal effects in the inflow conditions causes modulations in the reconnection rate and introduces time‐dependent effects The asymmetrically varying guide field alters the force balance between the current sheet and inflow region The outflow regions show nonlaminar exhaust structures induced by the changing inflow